Enhanced cortisol suppression following administration of low-dose dexamethasone in first-episode psychosis patients. (April 2013) - Phassouliotis, Christina; Garner, Belinda A; Phillips, Lisa J; Bendall, Sarah; Yun, Yang; Markulev, Connie; Kerr, Melissa; McGorry, Patrick D
Objective: Impaired regulation of the hypothalamic-pituitary-adrenal (HPA) axis and hyper-activity of this system have been described in patients with psychosis. Conversely, some psychiatric disorders such as post-traumatic stress disorder (PTSD) are characterised by HPA hypo-activity, which could be related to prior exposure to trauma. This study examined the cortisol response to the administration of low-dose dexamethasone in first-episode psychosis (FEP) patients and its relationship to childhood trauma. Method: The low-dose (0.25 mg) Dexamethasone Suppression Test (DST) was performed in 21 neuroleptic-naïve or minimally treated FEP patients and 20 healthy control participants. Childhood traumatic events were assessed in all participants using the Childhood Trauma Questionnaire (CTQ) and psychiatric symptoms were assessed in patients using standard rating scales. Results: FEP patients reported significantly higher rates of childhood trauma compared to controls ( p = 0.001) and exhibited lower basal (a.m.) cortisol ( p = 0.04) and an increased rate of cortisol hyper-suppression following dexamethasone administration compared to controls (33% (7/21) vs 5% (1/20), respectively; p = 0.04). There were no significant group differences in mean cortisol decline or percent cortisol suppression following the 0.25 mg DST. This study shows for the first time that a subset of patients experiencing their first episode of psychosis display enhanced cortisol suppression. Conclusions: These findings suggest there may be distinct profiles of HPA axis dysfunction in psychosis which should be further explored.